Luís Filipe de Abreu, desenho em contexto : conceptualização, narrativa e meios operativos - Abreu, Filipe Manuel Ribeiro de, 1970- (2017)
Having the opportunity to observe, in a privileged way, a unique set of studies and concepts which are less accessible to the public, this dissertation aims to explore some relevant concepts in the vast and diverse production of Luís Filipe de Abreu. Renowned for its great artistic and plastic richness, his work provides material that enables a thorough study in the fields of art and education. Regardless of time, different subjects or technical constraints, the underlying drawing of his creations is the common thread in this work. The conceptual techniques, the gesture, the geometrical rhetoric or the linear strokes and pure forms are concepts that have emerged from the development of this research, by showing particular characteristics in this author’s work. The themes and plastic media used are also subject of reflection and they complement this study. The multiplicity of possible options in the choice of the works presented has resulted in the need to find similarities or ideas that were transversal and enlightening. By focusing only on a few examples, this analysis is intended to show the existence of a set of theoretical and sensitive criteria used by Luís Filipe de Abreu that somehow provide an educational look at his work, that is a kind of drawing manual following the author's style